2019
DOI: 10.1088/1361-648x/ab22e7
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical study of magnetocaloric effect in Nd0.5Dy0.5FeO3

Abstract: A significant magnetocaloric effect (MCE) has been revealed in our investigation on polycrystalline Nd0.5Dy0.5FeO3 below 30 K. Observed magnetization of the system at low temperature is 32% higher than the expected average magnetization of NdFeO3 and DyFeO3. Such an enhancement in the magnetization led to a large change in magnetic entropy (10.4 Jkg−1 K−1) at 4 K. The observed entropy change is remarkable considering the higher natural abundance of Nd compared to that of Dy and negligible MCE seen in case of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…The compounds and orthoferrites containing Nd element usually show excellent magnetocaloric effect (MCE), , so we have also investigated the property of single crystal Nd 0.8 Pr 0.2 FeO 3 . In Figure , the representative isothermal magnetization curves are plotted when the magnetic fields along the a - and c -axes gradually increase to 70 kOe under different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds and orthoferrites containing Nd element usually show excellent magnetocaloric effect (MCE), , so we have also investigated the property of single crystal Nd 0.8 Pr 0.2 FeO 3 . In Figure , the representative isothermal magnetization curves are plotted when the magnetic fields along the a - and c -axes gradually increase to 70 kOe under different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum value of −ΔS m of the ErFeO 3 polycrystal 52 is 7.4 J/ kg•K, that of the DyFeO 3 polycrystal 52 is 11.4 J/kg•K, and that of the TmFeO 3 single crystal 42 is 11.93 J/kg•K. For rare-earthdoped compounds, 48 the maximum −ΔS m of Nd 0.5 Dy 0.5 FeO 3 is 10.4 J/kg•K, which is closed to the value of DyFeO 3 . Nevertheless, there are few reports on the magnetocaloric effect of NdFeO 3 single crystals and rare-earth-doped single crystals, and our results may fill the gap effectively in this field and can provide potential possibilities for the application of magnetic refrigeration materials.…”
Section: Magnetocaloric Effectmentioning
confidence: 96%
“…Some models analyze the MCE using different methods. Recently, the properties of MCE were studied by several theoretical methods, namely, mean-field theory (MFT) [20][21][22][23][24][25][26][27], effective-field theory (EFT) [28][29][30][31][32][33], Monte Carlo (MC) simulation [34][35][36][37][38][39] and first-principles calculations [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth orthoferrites materials RFeO 3 (R= rareearth ion), have shown potential for technologically relevant applications via observation of spin switching, spontaneous exchange bias and optically controlled ultrafast spin dynamics [1][2][3][4][5][6][7]. Additional important properties include large linear magneto-dielectric effect, spontaneous ferroelectric polarization, mutilferroicity, and magnetocaloric effect [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study by Wang et al [45] observed a long-to short-range ordering transition of Dy 3 concurrent to the magnetic field (along the c-axis) induced spin reorientation of the Fe 3+ sublattice. The magnetic field induced short range ordering of the Dy 3+ moments is responsible for the observed multiferroic phase induced by external magnetic field [10,45] In addition to the pure orthoferrites, doping and/or substitution at the Fe and/or R sites shows interesting variations in the structural, magnetic, and electronic properties, while the fundamental characteristic of ortho-ferrites is still retained [12,[56][57][58][59][60][61]. For instance, doping at the Fe-site with Mn has been studied and resulted in a systematic decrease of the Néel temperature [56,61], structural distortion due to Jahn-Teller effect [62], and modifies the preferred direction of Fe 3+ spins due to single ion anisotropy of Mn 3+ ions [56,63].…”
Section: Introductionmentioning
confidence: 99%